Crops pattern change and agricultural diversification: A case study of Domar Upazila, Nilphamari - Md. Naimur Rahman (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Cropping pattern means the proportions of area under various crops at a point of time. This paper provides a comprehensive assessment of crop pattern, crop productivity using climate, water and crop yield models. The existing studies present that climate change models with higher spatial resolution can be a way forward for future projections. Various types of statistics, other secondary data and primary questionnaire method was applied to measure and analysis the problem. The cropping pattern differs from macro to micro region, both in space and time and is governed largely by the physical, cultural and technological factors. For the purpose of agricultural regionalization and planning, it is necessary to divide the area/ region into homogeneous region on some well-defined basis. Increased crop production could be expected if the irrigated areas expansion prevails. In addition, it will lead degradation of the environmental phenomenon. The different crop pattern of this region varies the diversification of several discussed strength including soil, erosion, flooding, waterlogging, precipitation, source of irrigation and others. The areal unit of crop ranking is the dominant variables for first, second and third ranking. The importance of adoption of suitable cropping patterns in a developing country cannot be over emphasized. The horizontal expansion of agriculture is not possible without heavy capital investments. If the encouraging method does not get proper result for two or multiple crop pattern for extended areas of land then the food security could be ensured by zonation of crop pattern or judicious regulation.